(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
Mastering subject-specific terminology in English is essential for students of economics; however, many learners face considerable challenges in acquiring such specialized vocabulary. This article explores the root causes of lexical difficulties, their impact on the learning process, and strategies for overcoming them. Particular attention is given to students’ limited exposure to economic texts, lack of targeted exercises, and curricular gaps in language education. The author advocates for greater integration of language and subject content, proposing collaborative modules and practical tasks to improve students’ lexical competence.